PENGARUH HARGA JUAL PRODUK DAN BIAYA PROMOSI TERHADAP VOLUME PENJUALAN PADA PT. DRAGON PRODUK INDONESIA CARINGIN KABUPATEN BOGOR - Bria, Donatus Klau; Gemina, Dwi (Jurnal Visionida, 2017)
The objectives of the research are: 1) to analyze the development of selling price of product promotion cost and sales volume at PT Dragon Indonesia product; 2) to know the effect simultaneously effect of product selling price and promotion cost to sales volume at PT Dragon Produk Indonesia; 3) to analyze the effect of partial influence of selling price of product and promotion cost to sales volume at PT Dragon Produk Indonesia. The result of research shows the selling price of selling price of mop and broom during the year of 2015 from February to December fluctuated due to less stable market condition. Promotion costs for mop and broom during the year of 2015, from January to December continue to increase due to the company wants a maximum sales volume or profit. Sales volume, especially mop equipment within a year from January to December continued to fluctuate, ie in January sales of mops and brooms and in February decreased by 9 percent. Factor of selling price and promotion cost have positive and significant influence simultantly and partially to sales volume variable. Keywords: Price, Promotion, Sales Volume